DIE GRAFIESE VOORSTELLING VAN STROOMLYNE VAN 'N JOUKOWSKI-PROFIEL MET BEHULP VAN 'N REKENAAR - Strydom, D. (Scientia Militaria - South African Journal of Military Studies, 2012)
Where in the study of aerodynamics it is often necessary to represent flow patterns graphically, the writer illustrates how a desk calculator with plotting facilities and limited memory space can be used to this end. As an example he supplies a programme which can be used to plot flow patterns round a Joukowski wing profile.